Epstein Barr Virus Methods and Protocols - Minarovits, Janos; Niller, Hans Helmut (Methods in Molecular Biology, 2017)
This volume explores data from the applications of molecular biological methods and the applications of recent immunological and cytogenetic methods in Epstein-Barr Virus (EBV) that will offer readers possible new solutions to the unresolved problems in the EBV field. Chapters in this book cover topics such as: viral life cycle, latency, EBV-associated diseases and EBV diagnostics; in vitro methods including organotypic cultures for the analysis of EBV-epithelial cell interactions; identification of the interacting viral and cellular proteins using affinity purification-mass spectrometry methods; 3D telomere FISH; transcription analysis using high-throughput RNA sequencing, qPCR and nuclear run-on assay; analysis of viral and cellular microRNAs; isolation and characterization of exosomes and the assessment of their function; characterization of the viral genome by terminal repeat analysis and sequencing; the use of chromatin immunoprecipitation coupled sequencing (ChIP-Seq) for the analysis of Zta-DNA interactions; epigenetic analysis by bisulfite sequencing and ChIP; novel in vivo models for the study of EBV infection; and how immunological, virological, tissue culture and molecular methods can be combined to yield Good Manufacturing Practice-compliant EBV-specific T cells for the immunotherapy of EBV-associated post-transplant lymphoproliferative diseases (PTLD). Written in the highly successful Methods in Molecular Biology series format, chapters include introductions to their respective topics, lists of the necessary materials and reagents, step-by-step, readily reproducible laboratory protocols, and tips on troubleshooting and avoiding known pitfalls. Cutting-edge and comprehensive, Epstein Barr-Virus: Methods and Protocols is a valuable resource for anyone who is interested in this fascinating and evolving field